2023
DOI: 10.1038/s41598-023-36642-y
|View full text |Cite
|
Sign up to set email alerts
|

Tozorakimab (MEDI3506): an anti-IL-33 antibody that inhibits IL-33 signalling via ST2 and RAGE/EGFR to reduce inflammation and epithelial dysfunction

Abstract: Interleukin (IL)-33 is a broad-acting alarmin cytokine that can drive inflammatory responses following tissue damage or infection and is a promising target for treatment of inflammatory disease. Here, we describe the identification of tozorakimab (MEDI3506), a potent, human anti-IL-33 monoclonal antibody, which can inhibit reduced IL-33 (IL-33red) and oxidized IL-33 (IL-33ox) activities through distinct serum-stimulated 2 (ST2) and receptor for advanced glycation end products/epidermal growth factor receptor (… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
16
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 42 publications
(19 citation statements)
references
References 69 publications
2
16
0
1
Order By: Relevance
“…Despite the lower exposure observed in Japanese participants compared with non‐Japanese participants in phase I, no differences were found for target engagement in the serum for these 2 cohorts. Following multiple doses administered q2w, a slight accumulation of tozorakimab was noted based on the trough concentration, which was consistent with the estimated half‐life of the drug 13 …”
Section: Discussionsupporting
confidence: 76%
See 4 more Smart Citations
“…Despite the lower exposure observed in Japanese participants compared with non‐Japanese participants in phase I, no differences were found for target engagement in the serum for these 2 cohorts. Following multiple doses administered q2w, a slight accumulation of tozorakimab was noted based on the trough concentration, which was consistent with the estimated half‐life of the drug 13 …”
Section: Discussionsupporting
confidence: 76%
“…In an exploratory analysis, local target engagement was confirmed in nasal MLF samples through a numerical increase in the levels of the IL‐33/tozorakimab complex and a decrease in levels of both free IL‐33 red and IL‐33 ox . The relative levels of different forms of IL‐33 were consistent with the mechanism of action of tozorakimab and indicated that it prevented the formation of IL‐33 ox in patients with COPD 13 . Tozorakimab significantly reduced the serum levels of the COPD‐associated inflammatory cytokines IL‐5 and IL‐13, 25 confirming reductions in inflammatory biomarkers downstream of the IL‐33–ST2 pathway.…”
Section: Discussionsupporting
confidence: 61%
See 3 more Smart Citations